Near full light absorption and full charge collection in 1-micron thick quantum dot photodetector using intercalated graphene monolayer electrodes. Issue 8 (17th February 2020) - Chen, Wenjun; Ahn, Seungbae; Balingit, Marquez; Wang, Jiaying; Lockett, Malcolm; Vazquez-Mena, Oscar
Abstract : High charge collection efficiency in Vis and NIR using intercalated QD/Gr systems. Abstract : Quantum dots (QDs) offer several advantages in optoelectronics such as easy solution processing, strong light absorption and size tunable direct bandgap. However, their major limitation is their poor film mobility and short diffusion length (<250 nm). This has restricted the thickness of QD film to ∼200–300 nm due to the restriction that the diffusion length imposes on film thickness in order to keep efficient charge collection. Such thin films result in a significant decrease in quantum efficiency for λ > 700 nm in QDs photodetector and photovoltaic devices, causing a reduced photoresponsivity and a poor absorption towards the near-infrared part of the sunlight spectrum. Herein, we demonstrate 1 μm thick QDs photodetectors with intercalated graphene charge collectors that avoid the significant drop of quantum efficiency towards λ > 700 nm observed in most QD optoelectronic devices. The 1 μm thick intercalated QD films ensure strong light absorption while keeping efficient charge extraction with a quantum efficiency of 90%–70% from λ = 600 nm to 950 nm using intercalated graphene layers as charge collectors with interspacing distance of 100 nm. We demonstrate that the effect of graphene on light absorption is minimal. We achieve a time-modulation response of <1 s. We demonstrate that this technology can be implemented on flexible PET substrates, showing 70% of the original performance after 1000 times bending test. This system provides a novel approach towards high-performance photodetection and high conversion photovoltaic efficiency with quantum dots and on flexible substrates.